Chlorogenic Acid: HPLC Quantification and In Vitro Assessment of Proliferative and Migration Effects on Human Dermal Fibroblast Cells - Akpınar, Abdulbaki; Demirkaya Miloğlu, Fatma; Gündoğdu, Gülşah; Güven, Leyla; Bayrak, Burak; Kadıoğlu, Yücel (Cumhuriyet University, 2024)
Chlorogenic acid (CA) exhibits diverse biological activities, including antioxidant and antiinflammatory effects. This research aims to develop, optimize, and validate an HPLC method to quantify CA in methanol and investigate its in vitro proliferative and cell migration effects on human-dermal-fibroblast (HDF) cell lines in a dose-dependent manner. The HPLC experimental conditions were optimized using the central composite design (CCD) method for determining CA. Chromatographic separation occurred at a wavelength of 330 nm. Under the optimized conditions, the method exhibited linearity across a concentration range of 0.1-100 µg/mL, demonstrating sensitivity (LOQ:0.1µg/mL), precision (RSD%≤3.32), and accuracy (RE%≤4.05). To evaluate the in vitro proliferative and cell migration effects on HDFs, we employed the XTT cell proliferation assay and TAS-TOS commercial kits. The XTT assay revealed that CA displayed a proliferative effect within the concentration range of 75-250 µM (P <0.01), and at a concentration of 125 µM, TAS levels increased significantly (P<0.05). The scratch assay demonstrated that HDF cell migration increased at 12 h, with substantial closure of the wound area at 24 h when treated with CA concentrations between 75-125 µM. The results demonstrate that pure chlorogenic acid extracted from plants exhibits dose-dependent effects on cell proliferation, antioxidant, and cell migration
Keywords: Chlorogenic acid; HPLC; Experimental design; Central composite design; Quality Assurance, Chemometrics, Traceability and Metrological Chemistry; Kalite Kontrolü, Kemometri, İzlenebilirlik ve Metrolojik Kimya